Prevalence of eye injuries among locomotive drivers and Sentul Workshop workers in Keretapi Tanah Melayu in 1994, 1995 - Norizhar Kadarman,; K.G. Rampal, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross-sectional study was conducted to determine the prevalence of eye injuries and the factors influencing it among locomotive drivers and Sentul workshop workers of Keretapi Tanah Melayu in 1994. The sample was selected using convenient sampling technique. A total of 200 locomotive drivers and loo workshop workers were studied and the prevalence of eye injuries was 20.0%. The prevalence of eye injuries was significantly associated with mean age, types of job and length of services (p<0.05) .The prevalence of eye injuries was not significantly associated with ethnicity, level of education and level of knowledge on personal protective equipment (p>0.05). It was also found that brake block dust was the main causal agent among locomotive drivers while the causal agent for workshop workers was dust (p<0.05). The study also concluded that the mean annual sick leave among the workshop workers was higher than the locomotive drivers (p<0.05). Most of the eye injuries involved the left eye (56.7%) and the majority of these injuries were diagnosed as foreign bodies in the cornea (88.3%).None of those, injured was blinded or had serious complication.